Holiness in the Poetries of Philip Larkin (Global Journal of Human-Social Science, 2012)
The North Ship, was published in 1945, followed by two novels, Jill (1946) and A Girl in Winter (1947), but he came to
Keywords: holiness of the drab; of the quiet passion and persistence of submerged lives; of the heroism of compromise with frustration; passionate engagement wi